SINABANG DISTRICT COURT LAW ENFORCEMENT EFFORTS AGAINST FOUR-WHEEL VEHICLE EMBEZZLEMENT IN SIMEULUE REGENCY - Mimis Nofita Sari; Basri (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
Embezzlement in the Criminal Code is classified as a crime. The embezzlement is contained in Article 372 of the Criminal Code. The focus of this research is on law enforcement in dealing with criminal acts of embezzlement as well as inhibiting factors in law enforcement in handling criminal acts of embezzlement. Based on the results of research and discussion, it shows that law enforcement in handling criminal acts of embezzlement is carried out by means of crime prevention and prevention methods. The prevention approach is carried out through counseling and socialization in order to foster social responsibility for the residents of Simeulue Regency against the crime of embezzling four-wheeled vehicles. Legal counseling is especially carried out in areas prone to crime. The criminal approach is carried out through efforts to enforce the law of the Simeulue district in order to ensure that the perpetrators of the crime of embezzlement are legally processed in order to obtain criminal sanctions and guarantee legal certainty. Factors causing embezzlement of four-wheeled vehicles against law enforcement in handling criminal acts of embezzlement include: criminal sanctions in Article 372 of the Criminal Code that have not provided a deterrent effect, limited law enforcement agencies, limited state special budgets for law enforcement, lack of public awareness of the importance of understanding crime, society becomes a crime.